2012
DOI: 10.1111/j.1365-2966.2012.20827.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipole low-order g-mode instability of metal-poor low-mass main-sequence stars due to the mechanism

Abstract: We analysed the vibrational stability of metal‐poor low‐mass main‐sequence stars due to the ɛ mechanism. Since outer convection zones of metal‐poor stars are limited only to the very outer layers, uncertainty in the treatment of convection does not affect the result significantly. We found that the dipole g1 and g2 modes definitely become unstable due to the ɛ mechanism for . Besides that, we found that as the metallicity decreases the mass range of ɛ‐mechanism instability extends toward higher mass.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The absence of equilibrium conditions for a prolongated portion of time after the ZAMS is due to an additional mixing, providing more nuclear fuel for the He 3 combustion. The origin of this mixing is unclear and could be due to rotation, overshooting, or even nonlinear gravity modes, although this latter case seems less plausible considering the stability analyses of Sonoi & Shibahashi (2012). The seismic data alone cannot disentangle between these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of equilibrium conditions for a prolongated portion of time after the ZAMS is due to an additional mixing, providing more nuclear fuel for the He 3 combustion. The origin of this mixing is unclear and could be due to rotation, overshooting, or even nonlinear gravity modes, although this latter case seems less plausible considering the stability analyses of Sonoi & Shibahashi (2012). The seismic data alone cannot disentangle between these processes.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon was linked to the so-called "solar-spoon" mechanism presented by Dilke & Gough (1972) which was extensively discussed (see e.g. Ulrich & Rood 1973;Christensen-Dalsgaard et al 1974;Unno 1975;Shibahashi et al 1975, for a few references) and also investigated for Population III stars (Sonoi & Shibahashi 2012). In the latter case, the mixing results from the transport of chemicals by the nonlinear gravity modes generated by a form -mechanism due to the nuclear burning of 3 He.…”
Section: Survival Of a Convective Core In Kepler-444mentioning
confidence: 99%
“…Sonoi and Shibahashi (2012) found that the instability of the low-degree low-order gmodes due to the non-equilibrium 3 He burning is induced in a wider range of stellar mass as the metallicity decreases. In this case, the ratio ρ c / ρ decreases with decreasing the metallicity, since the star becomes compact as the opacity decreases.…”
Section: The -Mechanismmentioning
confidence: 99%
“…Such situation appears also in metal-poor low-mass main-sequence stars. Sonoi and Shibahashi (2012) found that the instability of the low-degree low-order gmodes due to the non-equilibrium 3 He burning is induced in a wider range of stellar mass as the metallicity decreases. In this case, the ratio ρ c / ρ decreases with decreasing the metallicity, since the star becomes compact as the opacity decreases.…”
Section: The -Mechanismmentioning
confidence: 98%